Reversal of Ischemic Hepatitis after Cardiac Surgery under Cardiopulmonary Bypass: A Case Report - Jaiswal, Lokesh Shekher; Pandit, Narendra; Prasad, Jagat Narayan (Journal of BP Koirala Institute of Health Sciences, 2020)
Acute hepatic failure due to ischemic hepatitis is associated with high mortality. The safety of cardiopulmonary bypass in this setting is not fully described. Here we report a case of a 21-year-old female who developed an acute fulminant hepatic failure due to ischemic hepatitis following a cardiogenic shock. She underwent subsequent successful mitral valve replacement under cardiopulmonary bypass, thus providing an evidence of its safety in acute fulminant hepatic failure.